Growth regulator and microfertilizers on Sage (Salvia officinalis L.) and Greater Burdock (Arctium lappa L.): effectiveness of complex application - N. I. Kovalev; G. P. Pushkina (Овощи России, 2020)
Relevance.Meeting the needs of the pharmaceutical industry with domestic medicinal raw materials is relevant. Methods.The aim of the study is to determine the effectiveness application by growth regulator, organomineral and microfertilizers on Sage (Salvia officinalis L.) and Greater Burdock (Arctium lappa L.) in conditions of Non-chernozem zone of the Russian Federation. The experimental part of the work was performed in Institute of Medicinal and Aromatic Plants in 2010-2011 and 2016-2017 by field experiments. On burdock we tested fertilizer Siliplant (0.5 l / ha): the first treatment was in the rosette phase, the second - after 20 days. On sage studied binary mixture of organomineral fertilizer EcoFys (1 l / ha) with fertilizer Zitovit (0.5 l / ha; applied in phase regrowth of plants) with following foliar application by complex microfertilizers Siliplant (0.5 l / ha) and growth regulator Zircon (40 ml / ha). The solution consumption is 300 l / ha.Results. The effectiveness of chelated form micro-fertilizers and organomineral fertilizers applied on various medicinal plants was shown. It has been established, that complex application by EcoFys+Zitovit (I treatment) and microfertilizer Siliplant with growth regulator Zircon (II treatment) can increase the productivity of Sage:  yield of grass raised by 23%, roots by 40%. Similar results were obtained on the Greater Burdock culture – treatment of plants with microfertilizer Siliplant allowed to increase the yield of roots by 28%, leaves-by 24%.